PENGARUH KARAKTERISTIK INDIVIDU, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA LUBUK PAKAM - Wendra Fatawa (Universitas Islam Islam Sumatera Utara, 2020)
The formulation of the problem in this research is how the influence of individual characteristic on employees performance. How influence of work environment on employees performance. How influence of work of load on employees performance. How influence of individual characteristic, work environment and work of load on employees performance. The purpose of this research is for know influence and analize of individual characteristic on employees performance. For know influence and analize of work environment on employees performance. For know influence and analize work of load on employees performance. For know influence and analize individual characteristic, work environment and work of load on employees performance. The sample in this research is 86 employees, with data analysis technique used is multiple linear regression analyze.The results of this research explain that individual characteristic effect has a positive and significant on employee performance. Work environment effect has a positive and significant on employee performance. Work of load effect has a positive and don’t significant on employee performance. Individual characteristic, work environment and work of load effect have a positive and significant on employee performance